A Comparison Between Calcium and Strontium Transport by the (Ca2+ + Mg2+)ATPase of the Basolateral Plasma Membrane of Renal Proximal Convoluted Tubules - José Roberto Meyer-Fernandes; Mauro Sola-Penna; Adalberto Vieyra (Membranes)
In this work, the utilization of calcium and strontium by the (Ca2+ + Mg2+)ATPase of the basolateral plasma membrane of renal proximal convoluted tubules were compared. [90Sr]Sr2+ and [45Ca]Ca2+ uptake by vesicles derived from this membrane were strictly dependent on ATP and Mg2+, and no other nucleotide was able to support the transport. Each cation inhibited the uptake of the other one in a purely competitive fashion (the same Vmax; increased K0.5), without causing a significant change in the influx rate. These results indicate that both cations bind at the same transport site on the enzyme, facing the cytosolic surface of the cell. The K0.5 for Sr2+ obtained for (Sr2+ + Mg2+)ATPase activity was 13.1 ± 0.2 µM and for Sr2+ uptake was 13.4 ± 0.1 µM. They were higher than K0.5 for Ca2+ obtained for (Ca2+ + Mg2+)ATPase activity (0.42 ± 0.03 µM) and for Ca2+ uptake (0.28 ± 0.02 µM). It is postulated that the lower ATPase affinity for Sr2+ is associated with greater steric difficulties for the occupation by this cation of the binding and transport sites, as a consequence of its greater crystal ionic radius (1.13 Å for Sr2+ against 0.99 Å for Ca2+).